PENGARUH AKTIVA PAJAK TANGGUHAN DAN BEBAN PAJAK TANGGUHAN TERHADAP EARNING MANAGEMENT (Studi Kasus pada Perusahaan Manufaktur Sub Sektor Otomotif dan Komponen yang terdafar di Bursa Efek Indonesia (BEI) Tahun 2019-2022) - Erlinda Ayu Mufadilah; Ahmad Yani; Dewi Wungkus Antasari (Jurnal Ekonomi dan Bisnis, 2023)
Companies currently have to face intense competition to survive in the global market, especially Indonesian manufacturing companies. Financial reports are a type of data used to evaluate the performance and financial stability of a company. This study examines the automotive components and components sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The automotive industry is one sub- sector of a multi-industry business, and its goal is to design, develop, build, market and sell motorized vehicles. This research is an associative quantitative research that aims to determine the effect between variables. The data in this study were obtained through financial reports listed on the Indonesia Stock Exchange. The sample technique used is purposive sampling. The research was conducted in the automotive and component sub-sector manufacturing companies in 2019-2022. The results showed that deferred tax assets (X1) had a significant effect on earning management (Y), deferred tax expenses (X2) had a significant effect on earning management (Y), deferred tax assets (X1) and deferred tax expenses (X2) ) had a significant effect on earnings management (Y). Based on these calculations, the variables of deferred tax assets (X1) and deferred tax liabilities (X2) have a simultaneous effect on earnings management (Y), which is equal to 28.8%. The rest (100% - 28.8% = 71.2%) is influenced by variousfactors.